Hybrid alkaline pulping enhances physiochemical, morphological, thermal, and mechanical properties of sugar palm fiber for papermaking - Hawanis, H. S.N.; Shamimimraphay, S. H.R.; Ilyas, R. A.; Jalil, Rafidah; Ibrahim, Rushdan; Zuhri, M. Y.M.; Azriena, H. A.A.; Abdul Majid, Rohah; Fatriasari, Widya (Elsevier B.V., 2025)
As global paper demand accelerates, concerns over deforestation from traditional wood pulp production underscore the urgent need for sustainable alternatives. This study explores sugar palm (Arenga pinnata) fibers, an abundant by-product in Malaysia, as a promising renewable source for papermaking. The research aims to optimize sodium hydroxide (NaOH) treatment to enhance fiber properties by effectively removing hemicellulose and lignin while modifying hydroxyl groups. Sugar palm fibers were treated with NaOH concentrations ranging from 0 % to 20 % to assess impacts on key paper properties, including tensile strength, brightness, opacity, and thickness. The hybrid pulping process integrated NaOH immersion, room temperature treatment, and refined mechanical pulping, followed by Sommerville screening, spinning, and blending. Advanced characterization techniques, Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD), Thermogravimetric Analysis (TGA), and Fourier-Transform Infrared Spectroscopy (FTIR), identified 15 % NaOH as the optimal concentration, yielding a 2.8 % increase in cellulose content, a 29.18 % rise in crystallinity index, and enhanced tensile strength to 2.86 kN/m. Thermal stability was also significantly improved, with degradation temperatures reaching 202.1°C and 580.2°C for the first and second degradation phases, respectively. These findings demonstrate that 15 % NaOH-treated sugar palm fibers present a viable, eco-friendly alternative to conventional wood pulp, contributing to sustainable advancements in the pulp and paper industry.